ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP NASABAH YANG MELAKUKAN KESALAHAN TRANSFER - Verawaty, Verawaty; ibrahim, Ukas (SCIENTIA JOURNAL, 2021)
Problems regarding transfer errors often occur in everyday life so that of course there is a need for a rule regarding the transfer of funds. Therefore, the government established a regulation regarding the transfer of funds as outlined in Law Number 3 of 2011 concerning Transfer of Funds. The solution that is always offered for the error in transferring funds is only in the form of punishment, no legal protection for customers who make wrong transfers, especially in returning the funds. The purpose of this study is to find out how the legal protection for banking customers who make transfer errors and to find out how to solve problems against customers who make transfer errors. The research method used is a normative legal research method. The complexity of the customer's error in transferring the funds resulted in the unfulfillment of a sense of justice, especially in the case that the recipient of the transfer of funds did not return the funds so that the form of loss experienced by the customer who made a transfer error was increasingly burdensome. Legal remedies that can be taken against this transfer error problem are to make efforts through litigation and non-litigation channels.